An electrochemical facile fabrication of platinum nanoparticle decorated reduced graphene oxide; application for enhanced electrochemical sensing of H2O2. Issue 128 (14th December 2015) - Palanisamy, Selvakumar; Lee, Hsin Fang; Chen, Shen-Ming; Thirumalraj, Balamurugan
Abstract : In the present work, we report a single step electrochemical fabrication of a platinum nanoparticle decorated reduced graphene oxide (RGO–PtNPs) composite for enhanced electrochemical sensing of hydrogen peroxide (H2 O2 ). Abstract : In the present work, we report a single step electrochemical fabrication of a platinum nanoparticle decorated reduced graphene oxide (RGO–PtNPs) composite for enhanced electrochemical sensing of hydrogen peroxide (H2 O2 ). The RGO–PtNPs composite was fabricated by the reduction of graphene oxide modified electrode in an electrolyte solution containing a 0.5 mM K2 PtCl6 solution with 1 mM KCl at a constant applied potential of −1.4 V for 300 s. The fabricated composite modified electrode was further characterized by scanning electron microscopy, elemental analysis and cyclic voltammetry. Compared with GO–PtNPs and PtNPs modified electrodes, the RGO–PtNPs composite modified electrode showed an enhanced electrocatalytic activity toward the reduction of H2 O2 . The amperometric response of the RGO–PtNPs composite modified electrode for the reduction of H2 O2 was linear over the concentration ranging from 0.05 to 750.6 μM with the limit of detection of 16 nM. The sensor reached its steady state current response within 2 s. The sensitivity of the sensor was calculated as 0.686 + 0.072 μA μM −1 cm −2 . The proposed sensor showed a satisfactory selectivity in the presence of biologically coactive compounds. In addition, the sensor also showed a good practicability toward the detection of H2 O2 in commercial contact lens solutions and human urine samples.